2015
DOI: 10.1614/ws-d-14-00187.1
|View full text |Cite
|
Sign up to set email alerts
|

Acetolactate Synthase–Inhibitor Resistance in Yellow Nutsedge (Cyperus esculentus): II—Physiognomy and Photoperiodic Response

Abstract: Yellow nutsedge is one of the most problematic weedy sedges in rice-soybean systems of the Mississippi Delta region. An acetolactate synthase (ALS)-inhibiting, herbicide-resistant (Res) yellow nutsedge biotype was recently documented in eastern Arkansas, which showed intermediary growth habit between yellow nutsedge and purple nutsedge and also exhibited differential photoperiodic sensitivity to flowering. The objectives of this study were to: (a) determine variation in reproductive characteristics of the Res … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…Dose-response assay by determining the GR 50 value is a classical approach to differentiating weed populations and natural variability of species in response to herbicides (Burgos et al 2013). Overall, these results indicate genetic differences in the response of yellow nutsedge biotypes to glyphosate, which are comparable to the findings of our previous experimentations regarding the phenological variations of yellow nutsedge biotypes under different photoperiodic regimes (Tehranchian et al 2015). Furthermore, similar responses of the Res and purple nutsedge plants to glyphosate may parallel their phylogenetic relationships and growth habit similarities that were exhibited in previous studies (Bagavathiannan et al 2015;.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Dose-response assay by determining the GR 50 value is a classical approach to differentiating weed populations and natural variability of species in response to herbicides (Burgos et al 2013). Overall, these results indicate genetic differences in the response of yellow nutsedge biotypes to glyphosate, which are comparable to the findings of our previous experimentations regarding the phenological variations of yellow nutsedge biotypes under different photoperiodic regimes (Tehranchian et al 2015). Furthermore, similar responses of the Res and purple nutsedge plants to glyphosate may parallel their phylogenetic relationships and growth habit similarities that were exhibited in previous studies (Bagavathiannan et al 2015;.…”
Section: Resultssupporting
confidence: 83%
“…Plant Propagation and Growth Conditions. Tubers of the Res and susceptible (Sus1, Sus2, and Sus3) yellow nutsedge biotypes were used (see Tehranchian et al 2015 for the history of these populations). Tubers of purple nutsedge were provided by Azlin Seed Company in Leland, MS. Tubers were initially sprouted in plastic flats (52.5 by 26.5 by 5.5 cm 3 ) filled with LC1 potting mix (Sun Gro Horticulture, Seba Beach, AB, Canada) in the greenhouse under a 14-h photoperiod at 35/25 C day/night temperatures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research demonstrated that Pro-197 and Trp-574 are common amino acid substitution sites that confer a high-level resistance to sulfonylureas (Corbett and François 2006;Heap 2015). It was reported that these amino acid substitutions in the ALS gene conferred resistance in C. difformis (Tehranchian et al 2015b), C. esculentus (Tehranchian et al 2014(Tehranchian et al , 2015a, and C. iria (Riar et al 2015). Our data revealed a mutation (CCC-TCC) in the ALS enzymes resulting in a Pro-197-Ser amino acid substitution codon in all R biotypes.…”
Section: Comparative Sequence Analysis Of the Genes Encoding Als Enzymessupporting
confidence: 49%
“…There are presently six Cyperus species, annual sedge (Cyperus compressus L.), fragrant flatsedge (Cyperus odoratus L.), rice flatsedge (Cyperus iria L.), smallflower umbrella sedge (Cyperus difformis L.), shortleaf spike sedge (Kyllinga brevifolia Rottb. ), and yellow nutsedge (Cyperus esculentus L.), that have developed resistance to ALS-inhibiting herbicides (Busi et al 2006;Heap 2015;Kuk et al 2004;McCullough et al 2016a;Merotto et al 2010;Ortiz et al 2015;Riar et al 2015;Tehranchian et al 2015aTehranchian et al , 2015b. Among these Cyperus species, C. compressus, C. odoratus, C. iria, and C. difformis are annuals, while the others are perennials.…”
Section: Introductionmentioning
confidence: 99%